Seismic Torsional Response of Asymmetrical Multi-Storey Frame Buildings - Sarvghad-Moghadam, Abdoreza (My University, 1998)
Seismic torsional response has always been a principal cause of structural failure in every major earthquake. There are numerous observations of damages caused by excessive torsional response in buildings, bridges, and lifeline structures. The torsion-induced failures have been especially catastrophic for multi-storey buildings because torsional response changes the uniform translational seismic floor displacements and causes concentration of demand in elements at the perimeter of the building. This often leads to failure of the over-loaded elements, which in turn initiates progressive collapse of the building. This study provides a conceptual explanation for the poor seismic performance of torsionally flexible asymmetric structures. These are buildings with a low level of torsional stiffness. Post-earthquake observations and also studies on single storey buildings have shown the vulnerability of these buildings to seismic damages. The study reported in this thesis extends the findings of previous research to multi-storey buildings and provides a theoretical foundation for understanding their seismic performance. Guidelines are developed and formulated to enable designers to identify torsionally flexible asymmetric buildings. This is of prime importance, as it is shown here that corrective measures taken by building codes in the form of statically applied torsional provisions are not effective for this type of structure. The future generation of codes for designing new structures and retrofitting existing structures will be performance based. A structure designed with such an approach has to meet a specific set of seismic performance criteria for a specific level of seismic hazard. Dynamic analyses of the building will be needed to assess the performance of the building at the many levels of seismic hazard. Preparation of input and interpretation of the large amount of output, resulting from an inelastic response analysis of multi-storey buildings is not practical, even for symmetric buildings. To overcome this, several simplified procedures based on inelastic static analyses are formulated in this thesis. Application of these procedures to some example multi-storey asymmetric buildings has shown that they are sufficiently simple and yet accurate for use in design offices. It is believed that a combination of these methods with sound engineering judgement will provide a practical and economical tool for the earthquake-resistant design profession to implement the performance-based design codes, currently being prepared by many countries, to protect life and property in urban centres in the event of an earthquake.
Keywords: Civil Engineering; Civil Engineering